2019
DOI: 10.1002/gcc.22665
|View full text |Cite
|
Sign up to set email alerts
|

Jumping translocations: Short telomeres or pathogenic TP53 variants as underlying mechanism in acute myeloid leukemia and myelodysplastic syndrome?

Abstract: Chromosomal rearrangements involving one donor chromosome and two or more recipient chromosomes are called jumping translocations. To date only few cases of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) with jumping translocations have been described and the underlying mechanisms remain unclear. Here, we analyzed 11 AML and 5 MDS cases with jumping translocations. The cases were analyzed by karyotyping, FISH, telomere length measurement, and next-generation sequencing with an AML/MDS gene pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…As shown by previous case series, the involvement of receptor chromosomes is highly variable, but the aforementioned receptor chromosomes have been described in other patients, especially chromosomes 13 and 15 [2][3][4][5] In our patient, mutations affecting genes involved in RNA splicing and DNA methylation (ASXL1, SF3B1, SRSF2) were observed [10]. These have been described as frequent "driver" mutations that appear at the beginning of the disease, both in MDS and AML [11,12].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…As shown by previous case series, the involvement of receptor chromosomes is highly variable, but the aforementioned receptor chromosomes have been described in other patients, especially chromosomes 13 and 15 [2][3][4][5] In our patient, mutations affecting genes involved in RNA splicing and DNA methylation (ASXL1, SF3B1, SRSF2) were observed [10]. These have been described as frequent "driver" mutations that appear at the beginning of the disease, both in MDS and AML [11,12].…”
Section: Discussionsupporting
confidence: 70%
“…Behrens et al [2] have also observed that in the receptor chromosomes there is generally a cut point in the pericentromeric or peritelomeric regions, but rarely outside of these locations. In line with other publications, they found significant shortening of telomeres in patients with JT, compared to controls in age-matched groups.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations